Limonin Alleviates Non-alcoholic Fatty Liver Disease by Reducing Lipid Accumulation, Suppressing Inflammation and Oxidative Stress - Li, Yunjia; Yang, Menghan; Lin, Haiyan; Yan, Weixin; Deng, Guanghui; Ye, Haixin; Shi, Hao; Wu, Chaofeng; Ma, Guoliang; Xu, Shu; Tan, Qinxiang; Gao, Zhuowei; et al. (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease and continues to rise in the worldwide. Limonin is a triterpenoid compound widely found in the fruits of citrus plants with a wide range of pharmacological effects, including anti-cancer, anti-inflammation, anti-viral, anti-oxidation and liver protection properties. However, the potential molecular mechanism of limonin on NAFLD in zebrafish remains unknown. In this study, zebrafish larvae were exposed to thioacetamide to establish an NAFLD model and the larvae were treated with limonin for 72 h simultaneously. The human liver cell line was stimulated with lipid mixture and meanwhile incubated with limonin for 24 h. The results showed that Limonin significantly reduced the accumulation of lipid droplets in the liver and down-regulated the levels of lipogenic transcription factors FASN and SREBP1 in NAFLD. Limonin suppressed macrophages infiltration and the down-regulated the relative expression levels of the pro-inflammatory factors IL-6, IL-1β and TNF-α secreted by macrophages. Besides, limonin could reversed the reduction of glutathione and the accumulation of reactive oxygen species through up-regulating NRF2/HO-1 signaling pathway in the liver. In conclusion, this study revealed that limonin has a protective effect on NAFLD due to its resistance to lipid deposition as well as antioxidant and anti-inflammatory actions.